Identification of Regional Shale Gas Sweet Spots and Unconventional Reservoirs Using Well Logs and Seismic Data - Elkaseh, Abdurahim (Curtin University, 2022)
To enable the oil and gas industry conduct exploration and identify potential shale gas sweet spots in a fast and cost-effective manner, the study developed a novel method for predicting in situ rock elastic properties. Specifically, taking the Canning Basin as a case study, correlation equations between static and dynamic rock elastic properties were developed. Such correlation equations can be used to accurately predict the actual in situ rock elastic properties, including the brittleness index.